2020
DOI: 10.3390/app10134424
|View full text |Cite
|
Sign up to set email alerts
|

Can We Rely on Flight Time to Measure Jumping Performance or Neuromuscular Fatigue-Overload in Professional Female Soccer Players?

Abstract: The main purpose of this study was to compare the validity of the take-off velocity method (TOV) measured with a force platform (FP) (gold standard) versus the flight time method (FT) in a vertical jump to measure jumping performance or neuromuscular fatigue-overload in professional female football players. For this purpose, we used a FP and a validated smartphone application (APP). A total of eight healthy professional female football players (aged 27.25 ± 6.48 years) participated in this study. All performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(65 reference statements)
1
5
3
Order By: Relevance
“…One key point of difference is the larger ICC 95% CI's seen in the present study compared to previous work (0.322-0.998), which at the lower end has shown to be greater than 0.680 [26] but typically greater than 0.990 for CMJ assessments [17,18]. Despite this, JH TIA compared JH MJ demonstrated low CV and systematic bias and 95% LoA's, adding to the body of the literature indicating that MyJump is valid when compared to TIA-derived jump height from a force platform.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One key point of difference is the larger ICC 95% CI's seen in the present study compared to previous work (0.322-0.998), which at the lower end has shown to be greater than 0.680 [26] but typically greater than 0.990 for CMJ assessments [17,18]. Despite this, JH TIA compared JH MJ demonstrated low CV and systematic bias and 95% LoA's, adding to the body of the literature indicating that MyJump is valid when compared to TIA-derived jump height from a force platform.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work that has compared the performance of MyJump to force-plate-derived TOV measures of jump height in adults is sparse, and the results are equivocal [18,26], whilst the data in the present study would appear to agree with the findings of Carlos-Vivas et al [18], who demonstrated excellent agreement despite a systematic bias where MyJump overestimated jump height derived from TIA. Interestingly, Armada-Cortés et al [26] contradicted the findings of the present and previous work [18], showing poor agreement and a significant mean difference between measures. Armada-Cortés et al [26] conducted validity analysis for combined SJ and CMJ.…”
Section: Discussionsupporting
confidence: 65%
“…The between-subject SD chosen for standardizing was not that of the subjects in our study, since they do not represent a sample of a population of competitive athletes. Instead, we obtained SD from recent studies on CMJ height of elite male [ 19 22 ] and female [ 23 26 ] football players. The SD were expressed as coefficients of variation (CV), converted to factors, log-transformed, averaged (via equally weighted variances) and back-transformed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a poor correlation has been observed between the vertical maximum force produced in a CMJ and the horizontal maximum force produced in a sprint, especially in high level athletes [53] such as the subjects in the present study. Further, a gold standard CMJ assessment tool (i.e., two force platforms coordinated) [69] might provide high-precision information regarding the difference in force application between the two lower limbs (i.e., previously injured vs. uninjured), and perhaps found data along the same line as the RSA test realized in the present study.…”
Section: Discussionmentioning
confidence: 73%